LncRNA-AK149641 regulates the secretion of tumor necrosis factor-α in P815 mast cells by targeting the nuclear factor-kappa B signaling pathway - Yao Zhou (Nature Portfolio, 2020)
Abstract Long noncoding RNAs play important roles in various biological processes. However, not much is known about their roles in inflammatory response. Mast cells, involved in innate and adaptive immunity, are one of the major effector cells in allergic inflammatory reactions and contribute to the pathogenesis of disorders, including asthma. In the present study, we aimed to verify and elucidate the function and possible role of a novel lncRNA, called lncRNA-AK149641, in the mechanism of lipopolysaccharide (LPS)-induced inflammatory response in P815 mast cells. The results showed that downregulating lncRNA-AK149641 decreased secretion of tumor necrosis factor-α into the supernatants of LPS-stimulated mast cells. Mechanistically, the activity of nuclear factor-kappa B (NF-κB) decreased after downregulating lncRNA-AK149641, as shown by western blot and electrophoretic mobility shift assays. Moreover, RNA binding protein immunoprecipitation (RIP) verified that lncRNA-AK149641 was able to bind to NF-κB in the nucleus. In conclusion, we demonstrated that lncRNA-AK149641 regulated LPS-induced inflammatory response in mast cells through the NF-κB signaling pathway.